Shear viscosity and spin sum rules in strongly interacting Fermi gases - Enss, Tilman (Arxiv, 2013)
Fermi gases with short-range interactions are ubiquitous in ultracold atomic systems. In the absence of spin-flipping processes the number of atoms in each spin species is conserved separately, and we discuss the associated Ward identities. For contact interactions the spin conductivity spectral function sigma_s(omega) has universal power-law tails at high frequency. We derive the spin f-sum rule and show that it is not affected by these tails in d<4 dimensions. Likewise the shear viscosity spectral function eta(omega) has universal tails; in contrast they modify the viscosity sum rule in a characteristic way.
Gesehen am 23.11.2017